South African Lecturers’ Views of ChatGPT: An AI Technology Used for Designing Online Assessments - du Plessis, Elize; Bayeck, Rebecca Y. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
Even while Artificial Intelligence (AI) has long been a part of our lives, it has recently received more attention thanks to the introduction of ChatGPT, a Chat Generative Pre-Trained Transformer, since its launch in November 2022. The focus of this study is to investigate the potential of ChatGPT to assess student-teacher learning, which looks at its use for online assessments in South Africa. It emphasises South African lecturers’ views of ChatGPT, an AI technology used for designing online assessments. The expansion of online assessments has brought about various adaptable tools and techniques, and ChatGPT provides benefits, including real-time interaction and personalised responses. Nevertheless, problems such as prejudices and circumstantial limitations still exist. Notwithstanding this, ChatGPT does well at assessing critical thinking by examining evidence-based reasoning and logical reliability. When integrating ChatGPT, ethical deliberations such as algorithmic transparency, data security, and privacy are crucial. Ten participants participated in a qualitative study that examined ChatGPT's effects on online assessment and student-teacher relationships using the Community of Inquiry (CoI) model. By presenting lecturers with AI-driven techniques and promoting innovation and technology integration, participants highlight their impact in promoting professional development. As a cooperative tool, ChatGPT offers tailored feedback, detailed instructions, and culturally appropriate rubrics that encourage critical thinking and introspection. It is essential, however, to contextualise its application to combat biases and cultural twists within the African educational environment. This ensures that rather than replacing student-teachers' knowledge, AI supports them using inclusive and valuable assessments.